Pengembangan E-Modul Interaktif Sistem Penerangan Berbasis Pembelajaran Berdiferensiasi - Rizki Maulana; Ranu Iskandar; Rizqi Fitri Naryanto (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The problem addressed in this study is the absence of digital technology-based learning resources that can accommodate the diverse learning styles of students in the TKRO (Light Vehicle Engineering) expertise program at SMK Texmaco Pemalang. The objective of this research is to develop a digital technology-based learning resource that accommodates students' diverse learning styles in the form of an interactive e-module on lighting systems based on differentiated instruction. Unlike previous e-modules, the developed interactive e-module integrates differentiated instruction in content delivery by utilizing various media in a flipbook format that is accessible through multiple digital devices. This study is categorized as research and development (R&D), employing the ADDIE development model. Data collection was conducted using a media assessment questionnaire with a four-point Likert scale, based on the Regulation of the Minister of Education and Culture Number 22 of 2022. The research subjects consisted of media experts and content experts. The data analysis technique used in this study was media validity analysis by calculating the percentage of assessment results and comparing them with the validity criteria table to determine the level of validity of the developed interactive e-module. The study resulted in an interactive e-module on lighting systems based on differentiated instruction that can be used in the learning process. This conclusion is supported by the combined validity assessment score from media and content experts, which reached 75% and falls into the "valid" category according to the feasibility criteria table.